Organizational support, social capital and innovative attitudes: A correlational study among workers in the city of Natal-RN (Research, Society and Development, 2021)
The search for innovative attitudes, as well as the incentive for the development of social relationships in the workplace, have been considered as mediating variables for organizational success. With this, recognition and appreciation actions about professional practices have become a constant practice in the corporate environment, however doubts about the benefits and real contributions to the physical and psychological well-being of professionals have arisen. Thus, this research aims to verify the influence of organizational support on social capital and innovative attitudes of workers who work in public and private organizations. Using the research instruments proposed by Siqueira (1995), Nahapiet and Ghoshal (1998), Fandiño, Formiga and Menezes (2018) on organizational support, social capital and innovative attitudes, the survey was applied through electronic questionnaires to 412 Brazilian workers from public and private organizations. The data treatment occurred through item discrimination analysis, content representation and relevant measures exploratory and confirmatory analysis. For this, SPSS software (version 21.0) was used for data analysis and it was observed that the development of innovative attitudes does not occur in a unique way, but associated with the organizational support that the company offers, making it clear the implementation of links between the organization's professionals, the construction of relationships types and the workers perception about the importance of this interaction, connection, and sharing of experience.